Intergenic and intronic DNA hypomethylated regions as putative regulators of imprinted domains. (23rd March 2018) - Bakshi, Arundhati; Bretz, Corey L; Cain, Terri L; Kim, Joomyeong
Aim: To investigate the regulatory potential of intergenic/intronic hypomethylated regions (iHMRs) within imprinted domains.Materials & methods: Based on the preliminary results of the histone modification and conservation profiles, we conducted reporter assays on the Peg3 and H19 domain iHMRs. The in vitro results were confirmed by the in vivo deletion of Peg3 -iHMR designed to test its function in the Peg3 imprinted domain.Results & conclusion: Initial bioinformatic analyses suggested that some iHMRs may be noncanonical enhancers for imprinted genes. Consistent with this, Peg3 - and H19 -iHMRs showed context-dependent promoter and enhancer activity. Further, deletion of Peg3 -iHMR resulted in allele- and sex-specific misregulation of several imprinted genes within the domain. Taken together, these results suggest that some iHMRs may function as domain-wide regulators for the associated imprinted domains. Graphical abstract: